2011
DOI: 10.1093/bja/aeq363
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between ultrasound-guided transversus abdominis plane and conventional ilioinguinal/iliohypogastric nerve blocks for day-case open inguinal hernia repair

Abstract: Ultrasound-guided TAP block provided better pain control than 'blind' IHN block after inguinal hernia repair but did not prevent the occurrence of chronic pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
126
1
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(136 citation statements)
references
References 31 publications
3
126
1
6
Order By: Relevance
“…6). Compared with the control group, the TAP block reduced the 24-hr pain score 20,30,31,39,48,62 by 1.7 (95% CI, App/IS = appendectomy /inguinal surgery; CD = Cesarean delivery; CI = confidence interval; I 2 = heterogeneity; IAW = inside abdominal wall; TAP = transversus abdominal plane block; US = ultrasound -2.4 to -1.0; P \ 0.001) and 24-hr morphine consumption 30,39,62 by 20.4 mg (95% CI, -29.7 to -11.1; P \ 0.001) ( Table 2).…”
Section: Transversus Abdominal Plane Block In Appendectomy and Inguinmentioning
confidence: 92%
See 2 more Smart Citations
“…6). Compared with the control group, the TAP block reduced the 24-hr pain score 20,30,31,39,48,62 by 1.7 (95% CI, App/IS = appendectomy /inguinal surgery; CD = Cesarean delivery; CI = confidence interval; I 2 = heterogeneity; IAW = inside abdominal wall; TAP = transversus abdominal plane block; US = ultrasound -2.4 to -1.0; P \ 0.001) and 24-hr morphine consumption 30,39,62 by 20.4 mg (95% CI, -29.7 to -11.1; P \ 0.001) ( Table 2).…”
Section: Transversus Abdominal Plane Block In Appendectomy and Inguinmentioning
confidence: 92%
“…In inguinal hernia surgery and appendectomy, compared with the control group, the overall analysis showed that the TAP block reduced the six-hour pain score 20,30,31,39 by 2.5 (95% CI, -4.7 to -1.2; P = 0.001) and the 12-hr pain score 20,30,31,39,48 by 3.9 (95% CI, -5.0 to -2.9; P\0.001) (Fig. 6).…”
Section: Transversus Abdominal Plane Block In Appendectomy and Inguinmentioning
confidence: 97%
See 1 more Smart Citation
“…A survey done about on 5000 patients found that 34.2% of patients visiting clinic have degenerative diseases and the second largest 22.5% of patients have chronic pain following the surgical procedure [1]. International Association for the study of pain (IASP) defines chronic pain as pain without apparent biological value that has persisted beyond the normal tissue; healing time is usually considered 3 months, however when it comes to CPOP, the working definition as mentioned in Table 1 written by Marcae and Davies, which is adopted and still frequently used [2].…”
Section: Introductionmentioning
confidence: 99%
“…[7] The transversus abdominis plane (TAP) block, a field block, has subsequently been used for postoperative pain relief in several abdominal surgeries such as large bowel resection, [8] open appendectomy, [9] retropubic prostatectomy, [10] hernia repair, [11] and cesarean section. [12] The blind technique was difficult and may carries potential risk of possible visceral injury, [13] so TAB block was done with ultrasound guidance To minimize these complication.…”
Section: Introductionmentioning
confidence: 99%